Day-to-day associations between mindfulness and perceived stress: insights from random intercept cross-lagged panel modeling - Borghi, Olaf; Voracek, Martin; Tran, Ulrich S. (Frontiers in Psychology, 2024)
Objective: Mindfulness is frequently seen as a protective factor of stress, but self-report measures of mindfulness may overlap with other related constructs, such as mental health, and could thus not only be a predictor, but also an outcome of stress. This study thus aimed to examine the longitudinal bidirectional associations between the use and perceived helpfulness of the four mindfulness facets Observe, Describe, Nonjudge, and Nonreact with daily perceived stress.Methods: Participants from a large (N = 1276) mixed student and community group sample filled out a brief daily diary over the time span of seven days. Bidirectional cross-lagged effects were investigated using the random-intercept cross-lagged panel model, an extension of the traditional cross-lagged panel model that allows to differentiate between stable between-unit differences and time-varying within-unit dynamics. In addition, we controlled for several baseline and sociodemographic confounders.Results: At the within-subject level, the use of Actaware was associated with higher perceived stress on the next day (β = .03, p = .029). The use (β = -.04, p = .025) and perceived helpfulness (β = -.05, p = .014) of Nonreact were associated with lower perceived stress on the next day. In turn, perceived stress was associated with lower perceived helpfulness of Describe (β = -.04, p = .037) and Nonreact (β = -.03, p = .038) on the next day. In addition, there were several residual correlations between mindfulness facets and perceived stress within days. At the between-subject level, there was a positive association between the random intercept of Describe and daily stress (r = .15, p = .003). In addition, while baseline perceived stress was negatively associated with the random intercepts of the mindfulness facets, two baseline components of mindfulness were not associated with the random intercept of perceived stress.On the currently investigated time scale, our results challenge prior results and assumptions regarding mindfulness as a buffering and protective factor against daily stress. With the exception of Nonreact, mindfulness was either positively associated with perceived stress, or in turn perceived stress appeared to interfere with the ability to stay mindful in daily life.